2008
DOI: 10.1002/pd.2151
|View full text |Cite
|
Sign up to set email alerts
|

OmniPlex—a new QF‐PCR assay for prenatal diagnosis of common aneuploidies based on evaluation of the heterozygosity of short tandem repeat loci in the Czech population

Abstract: OmniPlex assay significantly improved the QF-PCR methodology for rapid prenatal aneuploidy detection in the Czech population. Based on detected heterozygosity of markers used for QF-PCR in this population, OmniPlex is a robust assay for the detection of chromosomes 13, 18, 21, X and Y in a single reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Our results were comparable to those reported in the literature [9,10]. All seven cases which could not be confirmed by the molecular assay were either mosaic trisomy samples with a low level of the trisomic cell line (two cases) or unbalanced structural chromosomal rearrangements (five cases).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results were comparable to those reported in the literature [9,10]. All seven cases which could not be confirmed by the molecular assay were either mosaic trisomy samples with a low level of the trisomic cell line (two cases) or unbalanced structural chromosomal rearrangements (five cases).…”
Section: Discussionsupporting
confidence: 88%
“…QF-PCR tests are now performed in several prenatal centres in Europe for the detection of major numerical abnormalities affecting chromosomes 21, 18, 13, X and Y, with results provided within a 24 h period [6][7][8][9][10][11][12][13]. Despite the wide range of microsatellite marker multiplexes used by these laboratories, the assays are reported as both robust and reliable [4].…”
Section: Introductionmentioning
confidence: 99%
“…The authors then performed QF-PCR on 43,000 clinical samples and found 127 cases of trisomy 13, for which the QF-PCR results were consistent with those of the cytogenetic analysis (4). Putzova et al (17) found 11 and eight alleles of D13S305 and D13S631, respectively, in a Czech population, and the heterozygosity of each marker was 0.809 and 0.827. With regard to D13S305 and D13S634, Cho et al (18) found 11 and 10 alleles, respectively, in a Korean population, while Nasiri et al (10) observed nine and eight alleles, respectively, in an Iranian population.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the STR markers on the target chromosome is also crucial. In the present study, three STR markers distributed along the long arm of chromosome 13 were selected; these exhibited no overlap, which could have increased the possibility of detecting partial monosomy or trisomy (17). These STR markers, D13S305, D13S631 and D13S634, were selected from a total of eight STR markers, D13S631, D13S634, D13S258, D13S303, D13S256, D13S628, D13S742 and D13S305, based on their extensive use in the literature (4,7,10,15,(17)(18)(19), data on their repeat number, heterozygosity and genetic polymorphisms and our preliminary experiment, and were shown to be highly polymorphic in the Han population of Tianjin, China.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, these assays typically target only one locus per chromosome, precluding detection, and confirmation of trisomy. Trisomy detection using microsatellite genotyping requires multiple loci on each targeted chromosome, and at least two informative STR loci are usually required to confirm trisomy [9,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%